Role of Social Media in Medical Education – A Peep into the Pre-Covid 19 Scenario - Shah, Hijab (International Journal of Pathology, 2021)
Introduction: The platforms developed by social media are valued tools for educational purposes. However there is a lack of indigenous data especially in the Pre-COVID-19 situation that would give a glimpse of social media usage for educational purposes in Pakistan. Objective: To determine the awareness and frequency of use of social media for educational purposes by medical students and faculty in the Pre-COVID-19 period. Materials & Methods: It was a mixed method study comprising of self-constructed questionnaire, with closed ended questions for quantitative study and open ended questions for qualitative study. The study was carried out in Fazaia Medical College, Air University Islamabad, Pakistan over a period of 6 months (August 2018 to Jan 2019). Third year medical students and medical faculty participated in the study. Formal permission of the Institutional Review Board Bioethical Committee was obtained. Results: Ninety eight percent (70/71) students used social media for their educational purposes, 97% (69/71) & 77% (55/71) students believed that social media platforms increased their knowledge & skills respectively, 37% students (26/71) expressed time constraints with respect to use of social media in educational sphere, however 100% (28/28) faculty members were well aware of use of social media in medical education, whereas 60% (17/28) had time constraints, regarding the use of social media for education purposes. Themes and subthemes were derived from qualitative data and presented in a tabulated form. Conclusion: Use of social media in medical education is a challenging task for institutes and facilitators that requires adaptation